THE EFFECT OF COMPENSATION AND PERFORMANCE ASSESSMENT ON EMPLOYEE SATISFACTION THROUGH COMPETENCY AS A MEDIATION VARIABLE (CASE STUDY AT PT. VINDO INTERNATIONAL) - Purwanto, Setiyo; Hikmah Perkasa, Didin (Dinasti International Journal of Digital Business Management, 2021)
This research was conducted on the plastic manufacturing industry during the covid-19 pandemic. The purpose of this study was to examine the effect of compensation and performance appraisal on employee job satisfaction through competence as a mediating variable. The data in the study consisted of 150 populations and 109 samples in the study were employees of PT. Vindo International. Data analysis in this study used quantitative methods with the SmartPLS 3.0 test tool. Financial and non-financial compensation is part of the company's motivation to reward performance achievements. Providing appropriate compensation can provide employee job satisfaction and can trigger better performance. So that in the construction of this research a synergistic relationship is built in the provision of compensation accompanied by performance appraisals based on employee competencies, this will provide employee job satisfaction. Employee job satisfaction has an impact on performance, loyalty and awareness. All of this will shape the organizational culture to achieve company goals. The findings in this study are performance appraisals that are not based on employee competence can lead to individual subjectivity, this does not provide job satisfaction.